Lessons from Climate Reports for the Malaysian Medical Community - Jemilah, Mahmood *; Guinto, Renzo R * (Penerbit Universiti Sains Malaysia, 2022)
The period 2021–2022 is registering a number of alarming reports about the climate crisis. For the past year, the Intergovernmental Panel on Climate Change (IPCC), which is the United Nation’s body responsible for advancing climate science, published the three installments of their Sixth Assessment Report (AR6). These reports, authored by hundreds of scientists, comprised of thousands of pages and citing tens of thousands of research articles, are produced by the IPCC’s three working groups: i) Working Group 1 focusing on the physical science basis of climate change; ii) Working Group 2 examining climate change’s impacts and society’s vulnerability and adaptations to them; and iii) Working Group 3 dealing with current progress in relation to climate mitigation— meaning the reduction of greenhouse gas emissions in order to prevent the worsening of the climate emergency.